Increase Activity and Learning Outcomes With Collaboration Deployment Cooperative Learning Corners and Talking Stick/Meningkatkan Aktivitas dan Hasil Belajar Siswa Dengan Penerapan Kolaborasi Pembelajaran Kooperatif Model Corners dan Talking Stick - Siti Aisyah (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2015)
This study is a Classroom Action Research (CAR) which employed qualitative approach. This class action research was conducted into two cycles where in each cycle consisted of 4 stages namely planning, implementation, observation, and reflection. The subject of this study is the Tenth grade  students of TMP 1 on SMK Ahmad Yani Jabung as many as 24 students. The objective of this study is to describe: (1) the implementation of Corners and Talking Stick learning models, (2) student learning activities after participating in Corners and Talking Stick learning models, (3) student learning outcomes after following Corners and Talking Stick learning models, (4) constraints encountered during the implementation of Corners and Talking Stick learning models. The results of this study indicate that the implementation of Corners and Talking Stick learning models can increase the activity and student learning outcomes. The first meeting, the first cycle has 25.71 % and a second meeting in cycle 1 has 29.18 %  In the second cycle, the third meeting  student activity  reached 51.43 % to 58.89 % at the end of the meeting that was on the fourth meeting, (2) the results of the previous cognitive study, mastery learning percentage was 54.24 %  and increased to be79.17 % in the first cycle and the second cycle increased to be 91.67 %. Abstrak : Penelitian ini menggunakan pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas (PTK). Pelaksanaan penelitian tindakan kelas ini dilakukan 2 siklus dimana tiap siklus terdiri dari 4 tahap yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Subyek penelitiannya adalah siswa kelas X TPM 1 SMK Ahmad Yani Jabung, Kabupaten Malang sebanyak 24 siswa. Tujuan penelitian ini adalah untuk mendeskripsikan: (1) penerapan kolaborasi model pembelajaran Corners dan Talking Stick (2) aktivitas belajar siswa setelah mengikuti kolaborasi pembelajaran Corners dan Talking Stick (3) hasil belajar siswa setelah mengikuti kolaborasi pembelajaran Corners dan Talking Stick (4) Kendala-kendala yang dihadapi pada saat penerapan kolaborasi model pembelajaran Corners dan Talking Stick. Hasil penelitian ini menunjukkan bahwa penerapan kolaborasi pembelajaran  model Corners dan Talking Stick dapat meningkatkan aktivitas dan hasil belajar siswa. Siklus I pertemuan pertama aktivitas siswa 25,71% dan pertemuan kedua dalam siklus 1 sebesar 29,18%. Pada siklus II juga pertemuan ketiga aktivitas siswa dari 51,43% menjadi 58,89% di akhir pertemuan yaitu pertemuan keempat, hasil belajar ranak kognitif yang sebelumnya prosentase ketuntasan belajar 54,24% meningkat menjadi 79,17% pada siklus I dan pada siklus II meningkat menjadi 91,67%.